A vivid study on corporate social responsibility and its internal perception: Bibliometric analysis approach - Suong Huynh Thi Thu; Anh Le Xuan Quynh (Acta Psychologica, 2024)
Corporate Social Responsibility (CSR) is growing as a strategic tool creating a completive edge for any organizations. Together with CSR, employees are a fundamental driving force as they are responsible for achieving the business's objectives. This article primarily aims to provide directions for researchers in developing a theoretical framework and to assist new scholars exploring CSR-employee research by identifying key themes, publication trends, journals and authors relevant to this field. The authors used bibliographic coupling to scrutinize 399 articles on Scopus between 2013 and 2023. It is considered the rare study using bibliometric approach to review publications related to CSR and its internal perception review. The bibliographic coupling analysis identified five themes in CSR-employee relationship. These include CSR and Organization-related Employee Attitudes and Behaviors; CSR, Workplace Green Behavior and well-being; CSR and work perceptions; CSR and Employees' Behavioral Dynamics; CSR and Employee Volunteerism. Subsequently, this study offers insights into the most significant and current contributions to the field regarding the evolving landscape of research in the CSR-employee domain, identifying cutting-edge thematic topics in this area and enhancing understanding of its current state.